Concomitant chronic lymphocytic leukemia and Merkel cell carcinoma - Darko Antic; Jelena Jelicic; Vojin Vukovic; Gordana Pupic; Zorka Milovanovic; Biljana Mihaljevic (Dermatologica Sinica, 2015)
We present the case of a 69-year-old Caucasian man with a 5-year history of untreated chronic lymphocytic leukemia who presented with Merkel cell carcinoma on the right gluteal region. Six months after surgical treatment of Merkel cell carcinoma, we detected massive lymphadenopathy in the right retroperitoneum descending to the inguinum. A lymph node biopsy confirmed Merkel cell carcinoma relapse, and the patient was unsuccessfully treated with radiotherapy. As patients with chronic lymphocytic leukemia have a risk for developing a secondary malignancy, skin lesions need to be carefully examined and new lymphadenopathy must be pathohistologically evaluated.